Physio-Chemical and Mechanical Properties of Different Morphological Parts of Sugar Palm Fibre Reinforced Polyester Composites - Japar, Sahari (2011)
Recently, due to increase environmental concerns, scientists and technologists have placed much importance on the application of natural fibre composites especially in biocomposites. The purpose of this research is to study the properties of single fibre from different morphological parts of sugar palm tree and properties of sugar palm fibre from different parts reinforced unsaturated polyester composites. These studies have been done in order to evaluate the potentiality of fibre from different morphological parts of sugar palm tree i.e sugar palm frond (SPF), sugar palm bunch (SPB), sugar palm trunk (SPT) and black sugar palm fibre (ijuk) as which is can be used as eventual raw materials for the reinforcement of polymer matrix composites which are suitable in various applications such as building, automotive, furniture and packaging. The tensile, chemical and physical properties of single fibres from all parts were evaluated. The results showed that the highest tensile strength and tensile modulus were obtained from the SPF followed by SPB, ijuk and SPT. These results have been proven with the results of their chemical compositions where the highest cellulose content was obtained from SPF (66.49%) and followed by SPB (61.76%), ijuk (52.29%), and SPT (40.56%). The mechanical and physical properties of natural fibres from different parts of sugar palm tree reinforced unsaturated polyester composites which are SPF/PE, SPB/PE, SPT/PE and ijuk/PE have also been evaluated in this study. For tensile strength analysis, it is found that SPF/PE shared the higher value of 15.179 MPa (±2.425) followed by SPB/PE, ijuk/PE and SPT/PE with 12.809 MPa (±1.580), 11.473 MPa (±0.536) and 9.817 MPa (±1.890) respectively. The higher value of flexural strength and flexural modulus obtained from SPT/PE with the value of 41.906 MPa and 3.363 GPa respectively. For impact strength analysis, similar trends were found with the tensile stress and tensile strain results and SPF/PE showed the higher value of impact strength (8.091 kJ m-2) followed by SPB/PE, ijuk/PE and SPT/PE. In cases of physical properties, it is found that SPF/PE showed the higher value of water absorption and thickness swelling with the value of 1.57%, and 1.56% followed by SPB/PE (1.35%, 1.11%), ijuk/PE(0.65%, 0.76%) and SPT/PE (0.39%, 0.50%). Scanning electron microscopy (SEM) test were carried out after the mechanical test to observe the interface bonding of fibre and matrix.